A highly efficient alkaline HER Co–Mo bimetallic carbide catalyst with an optimized Mo d-orbital electronic state. Issue 20 (7th May 2019) - Liu, Gejun; Bai, Haipeng; Ji, Yujin; Wang, Lie; Wen, Yunzhou; Lin, Haiping; Zheng, Lirong; Li, Youyong; Zhang, Bo; Peng, Huisheng
Abstract : A Co–Mo bimetallic carbide catalyst with an optimized electronic state was fabricated and great alkaline HER performance was achieved. Abstract : Efficient catalysts for the alkaline hydrogen evolution reaction are continuously pursued to accelerate the kinetics of water splitting and enhance the conversion of renewable energy to chemical feedstock. Among numerous candidates, noble-metal-free Mo2 C catalysts are favored because of their low cost, abundance and similar d-orbital electronic state to the state of the art platinum. However, due to the high empty d-orbital density of high-valence Mo species in Mo2 C, the HER performance was impaired. We reason that introducing modulators into the Mo2 C framework that could decrease the empty d-orbital density and valence states of Mo may be an efficient way to optimize the HER energetics. Herein, inspired by the versatile electronic structures of 3d metals, we carried out first principles calculations using 3d metal Co as a dopant of Mo2 C to construct Co–Mo bimetallic carbide and found an enhanced HER activity after Co incorporation. We further synthesized a Co–Mo bimetallic carbide catalyst. The obtained catalysts achieved excellent alkaline HER performance with the lowest overpotential of −46 mV at −10 mA cm −2, a low Tafel slope of 46 mV dec −1 and great stability without any decay after a 500 hour reaction. The X-ray adsorption spectroscopy study showed that the valence state of Mo was decreased by the Co dopant and we propose that the decrease of Mo valence states should be the reason for the better HER performance of the bimetallic carbide than bulk Mo2 C.